BACK CALCULATION DETERMINATION OF THE MODULUS ELASTICITY OF LIMESTONE ROCK BASED ON PRESSUREMETER TEST DATA - Yusep Muslih Purwana; Akbar Dwi Anggoro; Niken Silmi Surjandari; Pontjo Utomo (Jurnal Riset Rekayasa Sipil, 2018)
Pressuremeter Test (PMT) is an in situ method of soil investigation that is used to determine the pressure and strain behavior of the soil or rock. At pseudo-elastic phase, this behavior can be described by the PMT’s output parameter, modulus presurremeter (EPMT). It has been realized for a long time that EPMT cannot be used directly to describe modulus elasticity (E) from the ground so a correction is needed. Menard and Rousseau suggested that Menard's α Factor be used to correct the value of EPMT that determined empirically according to soil type, density conditions, and deformation behavior of soil or rock when given pressure (rheological properties). Therefore, it is necessary to study PMT behavior along with Menard's α Factor values in a variety of more specific sample types. In this study Back Calculation will be performed on the value of E from PMT testing on limestone sedimentary rocks by remodeling PMT using Finite Element Method (FEM). Back Calculation is a mathematical recalculation process of estimating the value of a data from an event along with related parameters. The results of the study show that there is a good correlation between the modulus of elasticity of the results of PMT and the modulus of elasticity of the Back Calculation. Menard correction factor in this study is consistent with the results of previous research that is equal to 0.47 where this value increases with the increase in the depth of the test sample.